Uji Daya Terima Formulasi Klepon dengan Substitusi Tepung Kacang Arab, Tepung Kelor, dan Tepung Katuk sebagai Kudapan Alternatif Ibu Menyusui - Lailata, Irina; Adi, Annis Catur (Universitas Batanghari Jambi, 2024)
Exclusive breastfeeding in Indonesia is still relatively low. Intake of foods containing lactagogum for breastfeeding mothers is very necessary to facilitate breast milk and foods with sufficient protein and iron content can improve the quality of breast milk for babies. Utilizing local food ingredients with the nutritional content needed by breastfeeding mothers can help to increase the coverage of exclusive breastfeeding for babies. The aim of this research is to analyze the effect of substitution of local food ingredients, namely chickpeas, moringa, katuk and matcha on the acceptability, nutritional content, economic value and nutritional economic value of klepon cake as an alternative snack for breastfeeding mothers. This research is a pure experimental study on formula modification and quasi-experimental research on organoleptic tests with a completely randomized design (CRD) research design. There are five types of treatment with one control formula and four modified formulas with five repetitions. There were two types of panelists in this study, namely 3 panelists limited to preliminary research and 25 untrained panelists for follow-up research. Data collection techniques use organoleptic test forms and hedonic tests. Data analysis used the Friedman and Wilcoxson tests. The results of the research show that there is an effect of substitution of chickpea flour, moringa flour, katuk flour and matcha as alternative snacks for breastfeeding mothers.